2018
DOI: 10.1002/aoc.4321
|View full text |Cite
|
Sign up to set email alerts
|

Synergy Between DFT Calculations and Experimental Studies on the Optimized Structures and the Antibacterial Potential of Some Novel Tetra‐ and Penta Coordinated Organic‐ Inorganic Hybrid Complexes of Titanium(IV)

Abstract: The generation, structure, reactivity and antibacterial potential of some tetraand penta coordinated organic-inorganic hybrid complexes of titanium(IV) were comprehensively studied experimentally and theoretically by using density functional theory (DFT). These complexes were generated by the reaction of titanium isopropoxide with sterically demanding oximes of heterocyclic βdiketones in 1:1 molar ratio in dry benzene. The chemical structures of titanium complexes were systematically modified using relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Moreover, this reaction occurs in the aqueous phase and allows us to illustrate our method for a condensed-phase calculation. In the second system, we computed atomic charges using the data sets prepared in previous studies. , The data sets consist of 1421 different organic and inorganic molecules and can show the suitability of our fitting method for both organic and inorganic molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this reaction occurs in the aqueous phase and allows us to illustrate our method for a condensed-phase calculation. In the second system, we computed atomic charges using the data sets prepared in previous studies. , The data sets consist of 1421 different organic and inorganic molecules and can show the suitability of our fitting method for both organic and inorganic molecules.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the most characteristic FT-IR peaks of the vic-dioxime ligand (1) are observed at 3246, 1613, and 1242 cm À 1 , which correspond to υ(OÀ H), υ(C=N), and υ(NÀ O) stretching vibrations, respectively. [25,26] In the FT-IR spectra of metal-oxime complexes (2 -6), the four coordination sites of the metal ions were occupied by four nitrogen atoms of the free dioxime ligand (1). It was observed that infrared spectra of metal complexes (2 -6) of this free vic-dioxime ligand (1) were compared, some peaks belonging to the dioxime ligand disappeared, while some vibrational peaks shifted to low or high frequency after complexation.…”
Section: Spectroscopic Propertiesmentioning
confidence: 99%
“…A computational study is an essential tool for predicting the electronic properties and the structure of synthesized materials, [1,2] which find applications in various fields. [3,4] The chemistry of organic-inorganic hybrid complexes becomes the thrust area of research as these complexes exhibit improved medicinal properties and may use in drug design.…”
Section: Introductionmentioning
confidence: 99%